Evaluasi Kebijakan Sekolah Ramah Anak pada SMPN 18 Kota Tangerang Selatan - Vita Putri Oktaviani; Riswanda (Epistemik: Indonesian Journal of Social and Political Science, 2024)
The primary objective of this study is to assess the child-friendly school programs in South Tangerang City, with a specific focus on SMPN 18 South Tangerang City. The research aims to identify areas for improvement in order to enhance the effectiveness of these programs in the upcoming year. Leo Agustino (2023) Evaluation theory serves as the framework, encompassing elements such as apparatus or human resources, institutions, infrastructure and technology, finance, and regulations. Data for this study were collected through observation, interviews, and documentation, while the analysis involved data reduction, presentation, and drawing conclusions. The research site was SMPN 18 South Tangerang City. Key findings include: (1) Insufficient human resources in the implementation of child-friendly school programs; (2) Lack of collaboration and coordination among program implementers; (3) Adequate but insufficient Facilities, Infrastructure, and Technology, leading to disruptions in teaching and learning activities; (4) Financial shortcomings, necessitating independent fundraising by the school to support program activities; (5) Adherence to regulations governing child-friendly school programs, yet suboptimal impact due to prevalent physical and verbal violence in the school environment. In summary, the study sheds light on various challenges in the current implementation of child-friendly school programs at SMPN 18 South Tangerang City, providing valuable insights for improvement in the upcoming year.